Investigation on Flame Characteristics of a Flameless Combustor Ignition System Using Spiral Nozzle - AHMAD LAZIM, AMIRUL HAFIZI; KASANI, ADAM (Progress in Engineering Application and Technology, 2023)
Nowadays, combustion is one of the industrial procedures forheating, drying, shrinking, and polymerizing. Combustiongenerates hot air, which is subsequently channelled to selectedlocations for utilisation. The purpose of this study was todiscover and learn about the fire characteristics that occurwhen a spiral nozzle is utilised. The challenge of initiating the firein the combustor chamber was one of them. The researchobjectives are as follows: to establish the best operating methodfor igniting and firing up the combustor chamber. Experimentswere carried out in the automobile lab of the Faculty ofMechanical and Manufacturing Engineering FKMP during theproject's preliminary testing. To conduct out this investigation.This experiment was carried out using premixing (air pressureand Liquefied Petroleum Gas (LPG) and air pressure). For thisexperiment, an aapparatus such as 1 LPG gas barrel, an aircompressor, pipe tubing size 10, 2 flow metres for air and LPGgas, a spiral nozzle 12 inch, and a blow torch to light the fire. Fivethermocouples were employed, with a 5 cm space betweenthem. Researchers will be able to overcome the firing upproblem during preheating as a result of this research. damagingto the environment. The use of flameless combustion will help toextend the life of the equipment by ensuring that there is noflame present in the combustion chamber.